Spillover: From climate change to pandemics - Mary E. Wilson (Field Actions Science Reports)
Climate change will increase human infections and the risk of pandemics by affecting pathogenic microbes, their environmental reservoirs and animal hosts, and the mosquitoes and other vectors that transmit them. Climate-induced movement of arthropod vectors and range shifts of wildlife will place larger populations at higher risk for infectious spillover events. Recent epidemics and pandemics (e.g., HIV/AIDS, Covid, SARS, mpox, Ebola) have all originated from wildlife viruses carried by bats, rodents and other animals. While some areas in Africa are projected to become too hot for malaria transmission, changing climate will allow expansion of Aedes-transmitted viral infections, such as dengue, chikungunya, and Zika, into areas with large urban populations. Animals and plants are themselves susceptible to die-offs and even extinction from infections, jeopardizing food security and health.Another unknown is whether the vast permafrost, now melting, could become a source of novel microbes that are pathogenic for humans.Travel, trade, and migration contribute to the global movement of human and animal pathogens and vectors. These forces will be amplified by climate change, and climate-related loss of biodiversity will make ecosystems less resilient to invasive species.A One Health approach - considering together humans, animals, plants, and the shared environment – can inform surveillance, monitoring, research, and response, and help preserve human well-being while protecting the planet.